Needs Analysis of Electronic Module Based on PBL to Improve Students Collaboration Skills - Astuti, Linda Dwi; Damayanti, Indira Surya; Budiawanti, Sri (Kasuari: Physics Education Journal (KPEJ), 2024)
This study aims to analyze the needs of teachers and students for one of the learning media developments in the form of electronic modules based on Problem Based Learning (PBL) to improve students' collaboration skills. The needs analysis was carried out based on the first stage of the development research, namely analysis. The method in this study is a combination of qualitative and quantitative descriptive. The instruments used in the study were questionnaires and interview guides. The study was conducted involving 2 teachers and 108 students. Based on the results of the needs analysis that have been carried out, there are several problems, namely: 1) there are no teaching materials that can be used to improve student collaboration (2) there are no PBL-based teaching materials available, and (3) there is a need for the development of electronic modules. Based on these results, the researcher suggests the development of electronic modules based on PBL to improve students collaboration skills.